Metode Ekstraksi dan Karakterisasi Kitosan Dari Limbah Seafood : Kajian Pustaka - Ivana, Cheryn; Husin, Amelia S; Setiawati, Agustina (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Seafood waste is one of the common sources for chitosan production, such as crustaceans (shrimp, crab, and sea shells), squid cartilage, and others. Chitosan is a cationic biodegradable polymer which is biocompatible and has nontoxic properties to be applied in biological system. Chitosan, degraded from chitin, widely is used for drug delivery, tissue engineering (bone scaffold), food (coating film), agriculture (protection from harmful microorganisms), and pharmacological therapy such as an antibacterial agent for the human body. Chitosan is extracted with various methods such as chemical extraction, biological extraction, and microwave radiation extraction. Tthe characterization of chitosan can be known by percent yield, organoleptic test, dissolution, water content, and FTIR spectroscopy. The purpose of this review article is to overview the chitosan extraction method from environmental waste including the advantages and disadvantages of each method.